The industrialisation challenge for Africa: Towards a commodities based industrialisation path - Michael H. Morris; Judith Fessehaie (Journal of African Trade, 2014)
Since the turn of the millennium many African economies have been reintegrated into the world economy on a positive note and experienced substantial economic growth. This growth has primarily been concentrated in commodity exports. The central question facing African economies is how to use economic growth to foster industrialisation and thereby facilitate general development. This paper discusses the extent to which developing backward and forward linkages to the commodity sectors can contribute to its industrialisation project, in light of the past de-industrialisation process and recent trends in global commodity markets. It then reviews the theoretical criticism to resource-based industrialisation and proposes elements for a commodities based industrialisation strategy, including an analysis of the benefits of such strategy for Africa, and the factors contributing to its success.
Keywords: 330; African economies; Commodities; Exports; Industrialisation; Linkages